Effect of fuel concentration on supercapacitor cycling of Co3O4 fabricated via solution combustion method. (2023) - Yadav, Dheeraj Kumar; Maurya, Manu Prakash; Raitani, Karthik; Rastogi, Chandresh Kumar; Gyanprakash, Maurya; Hari Krishna, R.; Manjunatha, C.
Abstract: The reactivity of the cobalt oxide towards the supercapacitor cycling can be increased by increasing number of the reactive sites. It can be achieved via optimizing the energy of the surface, or tuning the reaction steps in the fabrication. Here we present a solution combustion method tuning the number of reactive sites via optimization of fuel to the precursor ratio. We used three ratios of precursor (cobalt nitrate) to fuel (ascorbic acid), i.e., 1:0.5 (S1), 1:2 (S2), and 1:4 (S3). The optimized sample S2 showed the maximum activity towards supercapacitor cycling. The increased activity is due to the increased concentration of Co +2 and Co +3 . Further, galvanostatic charge and discharge showed the increased charging and discharging time at the optimized fuel content sample (i.e., S2 sample). Also, the impedance analysis showed the increase in the reactivity was due to the decrease in the adsorption capacitance attributed to the adsorption reaction. The pseudo-capacitance obtained via the impedance analysis is highest for the S2 sample. Thus, the optimized fuel to the precursor ratio gives the highest active cobalt oxide for supercapacitor activity by increasing the Co +2 and Co +3 sites at the catalyst surface.